Process analysis and kinetic study on the reduction of iron ore powder by H2-CO mixtures using a fluidized bed-mass spectrometry coupling technique - Wang Shulin; Wang Linwei; Zhang Jiehan; Li Shiyuan (Fuel, 2026)

Injectable enzyme-triggered conductive hydrogel for restoring electrical homogeneity and functional recovery in myocardial infarction - Shun Xie; Fengjiao Deng; Ying Lu; Min Li; Shen Shen; Qin Wang; Weidong Li; Linwei Chen (Chemical Engineering Journal, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Controlling effect of the karst hydrogeological structure on karst collapse: a case study of the Chaoyang Tunnel, Guizhou - Lei Zhang; Xiqiong Xiang; Linwei Li; Wenjun Wang; Xiangquan Li (Carbonates and Evaporites, 2026)

Novel Hepatopancreas-Predominant C-Type Lectin (LvCTL) Contributes to Resistance Against Vibrio parahaemolyticus in Shrimp Litopenaeus vannamei - Ning Fu; Mengxin Xing; Yuyu Wang; Linwei Yang; Di Wang; Taolin Fan; Bang Xiao; Shengwen Niu (Fishes, 2026)
C-type lectins (CTLs) are important pattern recognition receptors (PRRs) involved in innate immune defense in crustaceans. In this study, a novel C-type lectin, designated LvCTL, was identified and functionally characterized from Litopenaeus vannamei. Sequence analysis revealed that the open reading frame (ORF) of LvCTL is 495 bp in length and encodes a 164-amino acid polypeptide containing a typical C-type lectin-like domain but lacking the classical carbohydrate-binding motifs. Notably, two novel EPF motifs were identified in the CTLD region, suggesting a potential non-canonical ligand recognition pattern. Phylogenetic analysis revealed that LvCTL clustered with other crustacean CTLs. Tissue expression analysis revealed that LvCTL exhibited the highest transcript level in the hepatopancreas. After immune stimulation, LvCTL expression in the hepatopancreas was significantly regulated by LPS, Vibrio parahaemolyticus, Staphylococcus aureus, WSSV and Poly(I: C), indicating its involvement in antimicrobial immune responses. RNA interference assays showed that knockdown of LvCTL significantly increased the bacterial burden and reduced the survival rate of shrimp after V. parahaemolyticus infection. Furthermore, recombinant LvCTL displayed broad bacterial binding activity to Gram-negative and Gram-positive bacteria and induced calcium-dependent agglutination of V. parahaemolyticus and S. aureus. Taken together, these results demonstrate that LvCTL functions as an important immune recognition molecule and contributes to antibacterial defense against V. parahaemolyticus in L. vannamei. These findings broaden our understanding of the functional diversity of shrimp CTLs and their contributions to crustacean innate immunity.

Early-Life Stages Amplify the Ecotoxicological Vulnerability of Freshwater Gastropods to the Agricultural Fungicide Prochloraz - Jiyuan Wang; Hairun Li; Jialu Xu; Yanlai Yao; Linwei Chen; Ruke Wang; Yuqing Shao; Lu Yang; Xiaofen Zhang; Xiaodong Yao; Lijun Lin; Hongyu Li (Journal of Hazardous Materials, 2026)

Natural radionuclides in atmospheric deposition and their responses to sandstorm events: A case study in Lanzhou - Linwei Li; Qiangqiang Zhong; Penggao Fang; Qiugui Wang; Wenyi Guo (Journal of Environmental Radioactivity, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Two unusual stereoisomeric dammarane-type triterpenoid saponins from the leaves of Panax japonicus (T. Nees) C. A. Mey - Yezi Ma; Linwei Dan; Wei Wang; Yuze Li; Xiaomei Song; Hao Fan; Dongdong Zhang (Natural Product Research, 2026)

Cosmic spike removal based on multi-feature fusion for long-time integrated Raman spectral detection - Huijie Wang; Xu Liu; Xujin Hu; Wenhui Sun; Shuang Xiong; Jinjin Wu; Linwei Shang; Jianhua Yin (Analytica Chimica Acta, 2026)

Experimental investigation of bubble morphology and instantaneous impact characteristics in submerged jets - Yongfei Yang; Wenxiao Wang; Weidong Shi; Xianglong Wu; Linwei Tan; Yupeng Cao; Yu Lu; Chunhui Ma (Ocean Engineering, 2026)

Failure pattern of ring-shaped leakage-induced ground collapse under varying pipeline fracture spacings in red clay areas: Insights from semiphysical modeling - Kai Wang; Linwei Li; Xiqiong Xiang; Yiping Wu; Fasheng Miao (Engineering Geology, 2026)

SAF-YOLO: Super-resolution augmented detection model with visual state space enhancement for safflower filament picking - Duan Mengyu; Wang Xiaorong; Qiu Linwei; Li Menghao; Chen Jinrong; He Liang (Precision Agriculture, 2026)

Warming increases viral diversity and the relative abundance of virulent viruses in deep soils - Yiqing Lv; Xiaomin Fan; Xiangyu Fan; Wenkuan Qin; Xudong Wang; Xin Sun; Biao Zhu; Linwei Wu (Soil Biology and Biochemistry, 2026)

Virus-inclusive microbial network relationships align with the stress gradient hypothesis in saline-alkali agroecosystems - Fang Li; Linwei Wu; Changlin Xu; Shuwen Guo; Jinhua Zhao; Yi Wang; Peipei Li; Biao Zhu (Soil Biology and Biochemistry, 2026)

Heteroaptamer recognition mediated strand displacement amplification for efficient electrochemical analysis of beta-2-microglobulin in breast milk - Yaqin Tang; Tingting He; Linwei Pan; Yanni Wang; Xiaolong Li; Xia Zhao; Daxiu Li; Baoting Dou (Food Chemistry, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Optimization of the initial performance of solid oxide fuel cells base on reduction and operating temperature - Peiyuan Liu; Xiaoyu Wang; Linwei Ma; Minfang Han (Chemical Engineering Journal, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Preparation of specific and sensitive monoclonal antibodies for thiamethoxam and development of immunoassay methods for detecting thiamethoxam in lake water, vegetables, and animal-derived foods - Jiacan Wang; Yiting Wang; Shixiang Wu; Linwei Zhang; Hao Wen; Hongfei Yang; Xu Wang; Dapeng Peng (Food Bioscience, 2026)

Effect of ultrasonication on the structure and stability of protein modified liposomes - Linwei Zhao; Libin Sun; Weining Wang; Mingzhe Pan; Lanxia Qin; Dianyu Yu (Food Hydrocolloids, 2026)

Effect of H2O(g) on the hydrogen reduction of iron ore in fluidized bed - Shiyi Ren; Linwei Wang; Jiehan Zhang; Shiyuan Li (Fuel, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Stress Behaviors of Cartilage with Defect and After Repair in Total Knee Under Compression Loading - Xianglong Lin; Shilei Wang; Bolun Liu; Lilan Gao; Linwei Lyu; Chunqiu Zhang (Journal of Medical and Biological Engineering, 2025)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

The unwetted height of transom-stern monohull ships and the Neumann–Michell ship flow computations - Chao Ma; Haolin Yang; Linwei Wang; Yingjiang Zhao; Jie Gong; Zhenlong Fang (Ocean Engineering, 2025)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

From Kelvin Wave Patterns to Ship Displacement: An Inverse Prediction Framework Based on a Hull Form Database - Chao Ma; Linwei Wang; Yingjiang Zhao; Haolin Yang; Haoqing Huang; Bohan Cao (Journal of Marine Science and Engineering, 2025)
The estimation of a ship’s displacement volume, ∇, from remote sensing data is of considerable practical value for maritime surveillance and vessel characterization. This paper introduces a practical framework for the inverse estimation of displacement volume from Kelvin ship waves, building upon a prior study through two key extensions. First, the wave amplitude function is recovered using Fourier series expansions combined with the stationary phase method. The displacement volume is then estimated via a two-step procedure: an initial estimate is obtained by identifying a hull with similar amplitude characteristics from a database, followed by a refinement that incorporates discrepancies between the target and candidate wave amplitude functions. In the case studied, the proposed approach achieves a prediction error of 4.02%, demonstrating its potential for non-invasive extraction of hull information from remote sensing data.

A novel LRR domain-containing C-type lectin gene with immune regulatory functions protects Penaeus vannamei against Vibrio parahaemolyticus infection - Kejia Weng; Ruoyu Liu; Chengqi Xiong; Yuxin Shi; Wenqian Chen; Chuanqi Wang; Linwei Yang (Fish & Shellfish Immunology, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Influence of interannual anomalies in late autumn Arctic sea ice concentration on Asian winter cold extremes - Cen Wang; Hui Su; Jianqiu Zheng; Linwei Jiang; Shiwei Yu; Yanjia Wang (Climate Dynamics, 2025)
In early 2008, densely populated areas of Asia suffered significant societal losses due to widespread cold extremes. Previous studies have suggested that variations in Arctic sea ice might influence the occurrence of Asian Winter Cold Extremes (AWCE). However, there is still debate over the precise nature and geographical specificity of these teleconnections. This study analyzes the frequency of AWCE from 1979 to 2024, and shows that it is significantly negatively correlated with anomalies in late autumn sea ice concentration (SIC) in the southern (SICS) Arctic on the interannual time scale. The potential physical mechanisms behind these correlations can be explained as follows: on a mean winter scale, anomalous decreases in SICS strengthens the ridge and deepens the trough over the Eurasian continent in the mid-troposphere, due to the excitation of Rossby waves. This, in turn, enhances anomalous northerly winds on the Siberian High’s eastern flank, particularly affecting Asia, thereby fostering conditions conducive to AWCE. On the synoptic scale, negative SICS anomalies promote more blocking highs over the northern Eurasian continent, thereby increasing the occurrence of AWCE.

Spermatogenesis and ultrastructure of the spermatozoa at three ploidy levels in the bivalve species, Corbicula fluminea - Jie Pi; Yangxin Tang; Ying Fu; Xu Wang; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Tissue and Cell, 2025)

Combined multispectral analysis and molecular docking to research the interaction of soybean isolate protein with different kinds of phospholipid liposomes and its effect on liposome properties - Linwei Zhao; Chunlei Liu; Tong Wang; Libin Sun; Fei Wu; Dianyu Yu (Food Chemistry, 2025)

DRAM2 inhibits white spot syndrome virus infection via activating autophagy in Penaeus vannamei - Xiyu Huang; Mingming Zhao; Jieyu Huang; Mingjian Liu; Linwei Yang; Chuanqi Wang (Fish & Shellfish Immunology, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Mechanism and kinetics of direct reduction reaction between H2/CO and hematite powder in a fluidized bed - Jiehan Zhang; Linwei Wang; Chuanhao Wang; Shiyi Ren; Shiyuan Li (Chemical Engineering Journal, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Combined effects of ammonia nitrogen, nitrite, salinity, and temperature negatively impact the growth, survival, physiological, and biochemical parameters, and hepatopancreatic structure of Litopenaeus vannamei - Xuenan Li; Linwei Wang; Xilin Dai (Aquaculture, 2025)

Molten-salt-assisted guanine-derived Fe-N-C electrocatalyst for oxygen reduction reaction - Linwei Zhang; Haixia Su; Fei Yang; Zhaodi Shen; Yunqin Yang; Wei Wang (Journal of Environmental Chemical Engineering, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

The Distribution Characteristics and Influencing Factors of the CO2 Fluxes Across the Sea–Air Interface in the Artificial Reefs Area of Sanheng Island - Mingdong Zhu; Kai Wang; Xu Zhao; Linwei Dai; Lei Chen; Hanyu Zhou (Journal of Marine Science and Engineering, 2024)
In order to study the impact of artificial reef construction on marine carbon sinks, a one-year monitoring and analysis were carried out in the Sanheng artificial reef areas of Shengsi Island. The main parameters observed were sea surface temperature, salinity, pH, total alkalinity (TA), and dissolved inorganic carbon (DIC). The partial pressure of CO2 (pCO2w) in the surface water and the CO2 flux (FCO2) across the sea–air interface were calculated and analyzed. The results showed that the annual range of surface water pCO2w was 34.48~501.53 μatm, and the partial pressure of CO2 decreases in the following order: winter, spring, autumn, summer. The FCO2 was significantly negatively correlated with temperature and significantly positively correlated with salinity and TA. The FCO2 in the four seasons decreases in the following order: winter, spring, autumn, summer. The annual sea–air flux in the survey area ranged from −108.79 to 41.74 mmol m−2 d−1. In winter, both the reef area and the control area displayed positive FCO2 values, indicating a source of CO2, while in the other three seasons, CO2 flux values were negative, indicating an overall CO2 sink. Additionally, in autumn, the reef area exhibited a stronger CO2 sink than the control area. The results indicated that the construction of artificial reefs has a certain carbon sink effect, with no significant difference in effectiveness between different artificial reef construction models.

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Records of Fukushima accident-derived cesium-137 in the Chukchi Sea sediment: Implication for a new time marker? - Xu Ren; Jinlong Wang; Gi Hoon Hong; Linwei Li; Qiangqiang Zhong; Dekun Huang; Tao Yu; Jinzhou Du (Science China Earth Sciences, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Complex phospholipid liposomes co-encapsulated of proanthocyanidins and α-tocopherol: Stability, antioxidant activity and in vitro digestion simulation - Linwei Zhao; Donghua Wang; Jiaye Yu; Xu Wang; Tong Wang; Dianyu Yu; Walid Elfalleh (Food Bioscience, 2024)

Extraction and purification, pharmacological action, synthesis and product development of salidroside: a review - Yaxiao Liu; Linwei Dan; Jiamei Tang; Zitong Yin; Longzhu Yang; Dongdong Zhang; Xiaomei Song; Wei Wang; Yuze Li (Medicinal Chemistry Research, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Increased FGL1 Expression Predicts Poor Prognosis and Promotes EMT in Head and Neck Squamous Cell Carcinoma - Zhiyong Pan; Weiqun Hu; Jinqiao Huang; Zhicong Zheng; Enrun Lin; PingPing Wang; Linwei Mao (Biochemical Genetics, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Research on the Penetration Coefficient During the Rock Drilling Process by Cyclic Impact - Jinguang Li; Yu Liu; Linwei Wang; Yumeng Sun; Xin Li; Junjie Wang (Rock Mechanics and Rock Engineering, 2024)

Structural effects of sulfonamides on the proliferation dynamics of sulfonamide resistance genes in the sequencing batch reactors and the mechanism - Ligui Wu; Mingyu Wang; Lingling Rong; Wenbiao Wang; Linwei Chen; Qiaofeng Wu; Haoyu Sun; Xiangfeng Huang; Xiaoming Zou (Journal of Environmental Sciences, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Contributions of residential traffic noise to depression and mental wellbeing in Hong Kong: A prospective cohort study - Jian Shi; Jianxiang Huang; Mengdi Guo; Linwei Tian; Jennifer Wang; Tze Wai Wong; Chris Webster; Gabriel M. Leung; Michael Y. Ni (Environmental Pollution, 2023)

Basigin binds bacteria and activates Dorsal signaling to promote antibacterial defense in Penaeus vannamei - Linwei Yang; Zi-ang Wang; Yushi Gan; Hongliang Zuo; Hengwei Deng; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Spatial pattern assessment of dengue fever risk in subtropical urban environments: The case of Hong Kong - Shi Yin; Junyi Hua; Chao Ren; Runxi Wang; André Ibáñez Weemaels; Benoit Guénard; Yuan Shi; Tsz-Cheung Lee; Hsiang-Yu Yuan; Ka Chun Chong; Linwei Tian (Landscape and Urban Planning, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Distinguishing the main components of submarine groundwater and estimating the corresponding fluxes based on radium tracing method—taking the Maowei Sea for example - Linwei Li; Jinzhou Du; Xilong Wang; Yanling Lao (Acta Oceanologica Sinica, 2023)

An Interdecadal Change in the Influence of the NAO on Atlantic-Induced Arctic Daily Warming around the Mid-1980s - Cen Wang; Baohua Ren; Gen Li; Jianqiu Zheng; Linwei Jiang; Di Xu (Advances in Atmospheric Sciences, 2023)

Iron phthalocyanine decorated porous biomass-derived carbon as highly effective electrocatalyst for oxygen reduction reaction - Linwei Zhang; Xudong Jiao; Guangjing He; Zhaodi Shen; Wei Wang (Journal of Environmental Chemical Engineering, 2023)

Current investigation status of oxy-fuel circulating fluidized bed combustion - Ge Chen; Li Shiyuan; Wang Linwei (Fuel, 2023)

Clinical Features and Skin Microbiome of Tinea Scrotum: An Observational Study of 113 Cases in China - Zixiang Si; Juan Bai; Linwei Wei; Honglei Zhao; Songting Wang; Bin Liu; Jingjing Xu; Hong Fang; Zongxin Ling; Jianjun Qiao (Mycopathologia, 2023)

Enhancement in the thermoelectric performance of ZrNiSn-based alloys through extra Zr-rich nanoprecipitates with superstructures - Ruonan Min; Yinlu Gao; Xue Jiang; Xiong Yang; Linwei Li; Huijun Kang; Enyu Guo; Zongning Chen; Tongmin Wang (Chemical Engineering Journal, 2023)

Slope Instability Analysis of the Qiongdongnan Basin in the Northern Part of the South China Sea: Implications for the Risk Evaluation of Deepwater Drilling - Linwei Ma; Shiguo Wu; Yanrui Liu; Jin Sun; Min Ouyang; Qingping Li; Yongpeng Qin; Dawei Wang (Journal of Ocean University of China, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Mapping conduits in two-dimensional heterogeneous karst aquifers using hydraulic tomography - Xintong Wang; Xiang-Zhao Kong; Linwei Hu; Zhenhao Xu (Journal of Hydrology, 2023)

Subsurface oxygen minima regulated by remineralization and bottom flushing along 123°E in the inner East China Sea - Bin Wang; Jianfang Chen; Haiyan Jin; Dewang Li; Shengquan Gao; Shichao Tian; Lin Sun; Haizhou Zhang; Linwei Li (Frontiers in Marine Science, 2023)
The summer hypoxia off the Changjiang Estuary is one of the largest coastal hypoxic systems in the world and has displayed spatial heterogeneity in recent years. Based on observation data in the summer of 2014, hypoxia was identified both in the bottom and mid-layers. Except for the typical bottom hypoxia in the submarine canyon, the subsurface oxygen minima (SOM) were captured in the mid-layer of 10~15 m, with lower dissolved oxygen in the mid-layer than at the bottom (30–50 m). This SOM phenomenon was located in the lower boundary of the pycnocline and above the Taiwan warm current (TWC) and Kuroshio subsurface water (KSSW). Due to the southern expansion of Changjiang diluted water (CDW), a high phytoplankton biomass (the maximum chlorophyll a of 25 μg L −1 , pH of 8.6, and DO of 11 mg L −1 ) band occupied the surface area along 123°E. By analyzing the 24-h continuous observation and high-resolution profile data, we revealed that the subsurface oxygen minima were predominantly controlled by remineralization and bottom-flushing effects. Fast local consumption occurred near the pycnocline layer, while the lateral transport of oxygen-rich ambient water replenished the bottom oxygen deficit from south to north. We summarize and contextualize three hot spots of hypoxia into a conceptual diagram and emphasize the influences of advection, mixing, and respiration on their location and severity. Overall, compared with the discussion about the low DO background of TWC/KSSW, this research highlights the flushing effects of TWC/KSSW that will reshape the hypoxia structure and alleviate the hypoxia severity in the south hypoxia area off the Changjiang Estuary.

Permafrost thaw with warming reduces microbial metabolic capacities in subsurface soils - Linwei Wu; Felix Yang; Jiajie Feng; Xuanyu Tao; Qi Qi; Cong Wang; Edward A. G. Schuur; Rosvel Bracho; Yi Huang; James R. Cole; James M. Tiedje; Jizhong Zhou (Molecular Ecology, 2022)
Microorganisms are major constituents of the total biomass in permafrost regions, whose underlain soils are frozen for at least two consecutive years. To understand potential microbial responses to climate change, here we examined microbial community compositions and functional capacities across four soil depths in an Alaska tundra site. We showed that a 5‐year warming treatment increased soil thaw depth by 25.7% ( p = .011) within the deep organic layer (15–25 cm). Concurrently, warming reduced 37% of bacterial abundance and 64% of fungal abundances in the deep organic layer, while it did not affect microbial abundance in other soil layers (i.e., 0–5, 5–15, and 45–55 cm). Warming treatment altered fungal community composition and microbial functional structure ( p p

Estimating submarine groundwater discharge at a subtropical river estuary along the Beibu Gulf, China - Xilong Wang; Kaijun Su; Juan Du; Linwei Li; Yanling Lao; Guizhen Ning; Li Bin (Acta Oceanologica Sinica, 2021)

Study of the Sensitive Properties of Marine Gas Hydrate Based on the Prestack Elastic Inversion - Siyou Tong; Jialin Wang; Linwei Li; Haiqi Zhang; Zhiqiang Wu; Yulan Shao (Journal of Ocean University of China, 2019)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Dissimilar responses of fungal and bacterial communities to soil transplantation simulating abrupt climate changes - Mengxin Zhao; Bo Sun; Linwei Wu; Feng Wang; Chongqing Wen; Mengmeng Wang; Yuting Liang; Lauren Hale; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2019)
Both fungi and bacteria play essential roles in regulating soil carbon cycling. To predict future carbon stability, it is imperative to understand their responses to environmental changes, which is subject to large uncertainty. As current global warming is causing range shifts toward higher latitudes, we conducted three reciprocal soil transplantation experiments over large transects in 2005 to simulate abrupt climate changes. Six years after soil transplantation, fungal biomass of transplanted soils showed a general pattern of changes from donor sites to destination, which were more obvious in bare fallow soils than in maize cropped soils. Strikingly, fungal community compositions were clustered by sites, demonstrating that fungi of transplanted soils acclimatized to the destination environment. Several fungal taxa displayed sharp changes in relative abundance, including Podospora , Chaetomium , Mortierella and Phialemonium . In contrast, bacterial communities remained largely unchanged. Consistent with the important role of fungi in affecting soil carbon cycling, 8.1%–10.0% of fungal genes encoding carbon‐decomposing enzymes were significantly ( p

Using Mirror Migration of OBS Data to Image the Deepwater Area of South China Sea - Siyou Tong; Chuanxi Sun; Linwei Li; Dazhen Xu; Jie Wang (Journal of Earth Science, 2018)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Expanding indole diversity: direct 1-step synthesis of 1,2-fused indoles and spiroindolines from 2-halo anilines for fast SAR antiviral elucidation against tobacco mosaic virus (TMV) - Linwei Chen; Yongxian Liu; Hongjian Song; Yuxiu Liu; Lizhong Wang; Qingmin Wang (Molecular Diversity, 2017)

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.